A Generic Acceleration Framework for Grid-based Wind Farm Layout Optimization - Du, Yunfei; Shen, Xinwei; Luo, Yangfan; Huang, Zehai; Lu, Boan (IEEE transactions on sustainable energy, 2025)
This letter proposes an acceleration framework for the grid model of wind farm layout optimization (WFLO-GM), using consensus-based scenario decomposition and an ℓp-box equivalence to enable efficient binary integer programming (BIP) via alternating direction method of multipliers (ADMM). Case studies at different model scales show that compared to the direct solution, the proposed framework reduces solution time by more than 20 times while preserving optimality, and achieves better layout results in large-scale WFLO-GM.